FINANCIAL SUSTAINABILITY OF CREATIVE ECONOMY MSMEs IN THE CULINARY SUBSECTOR: A SYSTEMATIC LITERATURE REVIEW - Ferry Aprianto; Andrian Saputra; Riyaldi Januar; Muhammad Raisfron; Rama Eka Febrian (BEMJ: Business, Entrepreneurship, and Management Journal, 2025)
Abstract This study examines the development of research on the financial sustainability of creative economy micro, small, and medium enterprises (MSMEs), with a focus on the culinary subsector. A Systematic Literature Review (SLR) was conducted using a structured procedure guided by the PRISMA framework to synthesize relevant academic publications. The findings indicate that MSMEs dominate the research focus, particularly in relation to economic resilience and post-crisis recovery. However, studies addressing financial sustainability, financial management practices, and culinary-specific contexts remain limited. The literature is also dominated by quantitative approaches, highlighting the need for more integrative and context-sensitive research to strengthen the long-term financial sustainability of culinary MSMEs.